The shorter writings - Xenophon (Agora editions (Cornell University Press), 2018)
This book contains new, annotated, and literal yet accessible translations of Xenophon's eight shorter writings, accompanied by interpretive essays that reveal these works to be masterful achievements by a serious thinker of the first rank who raises ...